Effects of leucine supplemented diet on intestinal absorption in tumor bearing pregnant rats - Ventrucci, Gislaine (BioMed Central, 2002)
BACKGROUND: It is known that amino acid oxidation is increased in tumor-bearing rat muscles and that leucine is an important ketogenic amino acid that provides energy to the skeletal muscle. METHODS: To evaluate the effects of a leucine supplemented diet on the intestinal absorption alterations produced by Walker 256, growing pregnant rats were distributed into six groups. Three pregnant groups received a normal protein diet (18% protein): pregnant (N), tumor-bearing (WN), pair-fed rats (Np). Three other pregnant groups were fed a diet supplemented with 3% leucine (15% protein plus 3% leucine): leucine (L), tumor-bearing (WL) and pair-fed with leucine (Lp). Non pregnant rats (C), which received a normal protein diet, were used as a control group. After 20 days, the animals were submitted to intestinal perfusion to measure leucine, methionine and glucose absorption. RESULTS: Tumor-bearing pregnant rats showed impairment in food intake, body weight gain and muscle protein content, which were less accentuated in WL than in WN rats. These metabolic changes led to reduction in both fetal and tumor development. Leucine absorption slightly increased in WN group. In spite of having a significant decrease in leucine and methionine absorption compared to L, the WL group has shown a higher absorption rate of methionine than WN group, probably due to the ingestion of the leucine supplemented diet inducing this amino acid uptake. Glucose absorption was reduced in both tumor-bearing groups. CONCLUSIONS: Leucine supplementation during pregnancy in tumor-bearing rats promoted high leucine absorption, increasing the availability of the amino acid for neoplasic cells and, mainly, for fetus and host utilization. This may have contributed to the better preservation of body weight gain, food intake and muscle protein observed in the supplemented rats in relation to the non-supplemented ones.